Model Kemitraan Sekolah Cerdas Bencana Dalam Penanggulangan Bencana Gempa Bumi dan Tsunami di Kota Padang - Firanda Catriona; Ria Ariany; Roni Ekha Putera (Universitas Serang Raya, 2021)
Partnership in disaster mitigation is important considering that disaster risk reduction efforts are the responsibility of all parties. This study aims to analyze and describe the partnerships of government, NGOs, and Non-Government organization in disaster smart schools in improving earthquake and tsunami disaster preparedness in school located in the red zone in Padang City. This research is motivated by the city of Padang which is a disaster-prone area. Therefore, the municipal government of Padang has the responsibility to protect its citizens from the threat of disaster. The research design used is a descriptive method with a qualitative approach. This research design is considered capable of explaining this research in depth. The results showed that overall the partnership between BPBD Padang and its partners namely Kogami, Jemari Sakato, POF BPBD West Sumatra, and DRRI, in an effort to improve preparedness in schools has gone quite well. The partnership in this study uses a mutualistic partnership models because the partners are aware of the important aspects of partnership, namely providing mutual benefit and getting more benefits so that they are able to optimally achieve the goals of Disaster Smart Schools.